Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genome characterization of the selected long- and short-sleep mouse lines - Robin Dowell; Aaron Odell; Phillip Richmond; Daniel Malmer; Eitan Halper-Stromberg; Beth Bennett; Colin Larson; Sonia Leach; Richard A. Radcliffe (Mammalian Genome, 2016)

Influence of sex on genetic regulation of “drinking in the dark” alcohol consumption - Lauren A. Vanderlinden; Laura M. Saba; Beth Bennett; Paula L. Hoffman; Boris Tabakoff (Mammalian Genome, 2015)

Exome sequencing and arrayCGH detection of gene sequence and copy number variation between ILS and ISS mouse strains - Laura Dumas; C. Michael Dickens; Nathan Anderson; Jonathan Davis; Beth Bennett; Richard A. Radcliffe; James M. Sikela (Mammalian Genome, 2014)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Expression profiling identifies novel candidate genes for ethanol sensitivity QTLs - Erik J. MacLaren; Beth Bennett; Thomas E. Johnson; James M. Sikela (Mammalian Genome, 2006)

Genetics of body weight in the LXS recombinant inbred mouse strains - Beth Bennett; Phyllis J. Carosone-Link; Lu Lu; Elissa J. Chesler; Thomas E. Johnson (Mammalian Genome, 2005)

Genetic structure of the LXS panel of recombinant inbred mouse strains: a powerful resource for complex trait analysis - Robert W. Williams; Beth Bennett; Lu Lu; Jing Gu; John C. DeFries; Phyllis J. Carosone–Link; Brad A. Rikke; John K. Belknap; Thomas E. Johnson (Mammalian Genome, 2004)

Voltage-gated Na + channels confer invasive properties on human prostate cancer cells - Eric S. Bennett; Beth A. Smith; Jean M. Harper (Pflügers Archiv - European Journal of Physiology, 2004)

High-throughput sequence identification of gene coding variants within alcohol-related QTLs - Marissa A. Ehringer; Jessica Thompson; Otakuye Conroy; Yan Xu; Fan Yang; Jennifer Canniff; Mary Beeson; Lena Gordon; Beth Bennett; Thomas E. Johnson; James M. Sikela (Mammalian Genome, 2001)

Identification of peak bone mass QTL in a spontaneously osteoporotic mouse strain - Motoyuki Shimizu; Keiichi Higuchi; Beth Bennett; Chen Xia; Tadao Tsuboyama; Soichiro Kasai; Takuya Chiba; Hiromi Fujisawa; Kumiko Kogishi; Haruo Kitado; Mitsutoshi Kimoto; Norikazu Takeda; et al. (Mammalian Genome, 1999)

Development of congenics for hypnotic sensitivity to ethanol by QTL-marker-assisted counter selection - Beth Bennett *, , Thomas E. Johns (Mammalian Genome, 1998)